2015
DOI: 10.1007/s10865-015-9657-y
|View full text |Cite
|
Sign up to set email alerts
|

For better or for worse: a longitudinal study on dyadic coping and quality of life among couples with a partner suffering from COPD

Abstract: In chronic obstructive pulmonary disease, impairments of dyadic coping are associated with reduced quality of life. However, existing studies have a cross-sectional design. The present study explores changes in dyadic coping over time and its long-term effects on quality of life of both patients suffering from COPD and their partners. Dyadic coping, psychological distress, health-related quality of life, and exercise capacity were assessed in 63 patients suffering from COPD with their partners, at baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 40 publications
(49 reference statements)
4
55
0
Order By: Relevance
“…A few studies have shown that the relationship between the spouses and their combined ability to cope with the disease is associated with the psychological distress and low quality of life of both COPD patient and informal caregiver spouse (Meier et al 2011, Vaske et al 2015. With this insight, we find the principles of shared decision-making (SDM) valuable in supporting the informal caregiver spouses and responding to their desired needs for support.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A few studies have shown that the relationship between the spouses and their combined ability to cope with the disease is associated with the psychological distress and low quality of life of both COPD patient and informal caregiver spouse (Meier et al 2011, Vaske et al 2015. With this insight, we find the principles of shared decision-making (SDM) valuable in supporting the informal caregiver spouses and responding to their desired needs for support.…”
Section: Discussionmentioning
confidence: 94%
“…, Vaske et al . ). With this insight, we find the principles of shared decision‐making (SDM) valuable in supporting the informal caregiver spouses and responding to their desired needs for support.…”
Section: Discussionmentioning
confidence: 97%
“…Contrary to our hypotheses, the evidence for the mediating role of dyadic coping between financial strain and psychological distress was weaker, in that negative dyadic coping by men was the only mediator found and this was an actor effect. Although negative dyadic coping has been related to more psychological symptoms in several studies (e.g., Rottmann et al, ; Vaske et al, ), especially so for men (Bodenmann, Charvoz, Widmer, & Bradbury, ), Bodenmann, Meuwly, and Kayser () have also found that the relationship between dyadic coping and general distress is weaker than that between dyadic coping and relationship satisfaction. They speculate that general levels of distress may be more a function of individual coping rather than dyadic coping, whereas the reverse may hold true for relationship satisfaction.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, patients who reported engaging in common dyadic coping had higher relationship quality and fewer depressive symptoms and so did their partners. Studying a different health population, COPD patients, Vaske et al () found that a care partner's quality of life at follow‐up was also negatively associated with the patient's negative dyadic coping and positively related to the care partner's delegated dyadic coping as rated by patients.…”
Section: Review Of Recent Research and Theoretical Perspectives On Dymentioning
confidence: 99%